Pendampingan Klien Penyalahguna Narkoba Melalui Pendekatan Case Work untuk Mendukung Proses Pemulihan di Yayasan Kiki Alam Jaya (Pusat Rehabilitasi Korban Penyalahgunaan NAPZA) - Canda C; Novita Sari (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Drug abuse remains a significant social problem that affects various aspects of an individual’s life, including physical health, psychological well-being, and social functioning. The rehabilitation process is not only aimed at stopping substance use but also at restoring an individual’s ability to perform social roles and functions effectively. This article aims to describe the assistance process provided to a client with a history of drug abuse through a social case work approach at Yayasan Kiki Alam Jaya, Medan. This study employed a qualitative descriptive method. Data were collected through in-depth interviews, observation, documentation, and assessment instruments, including the Biopsychosocial-Spiritual Assessment (BPSS), the University of Rhode Island Change Assessment (URICA), and the World Health Organization Quality of Life (WHOQOL). The assessment results indicated that the client experienced difficulties in emotional regulation, low family trust due to a history of relapse, and exposure to a social environment that increased the risk of recurring drug use. Based on the assessment findings and SWOT analysis, the interventions implemented included individual counseling using Cognitive Behaviour Therapy (CBT), Motivational Interviewing, emotional control training and drug-related psychoeducation, family dialogue, and post-rehabilitation planning. The assistance process was carried out through the stages of social case work, namely the study phase, assessment phase, intervention phase, and termination phase. The results demonstrated improvements in the client’s awareness of emotional management, understanding of the consequences of drug abuse, and motivation to maintain recovery while rebuilding relationships with family members.